Preparation method of titanium black core-shell structure conductive particles applied to ACF (anisotropic conductive film)

By using the titanium oxide core-shell structure conductive particles preparation method in ACF conductive microspheres, the problem of poor long-term stability and reliability of ACF is solved, and the effects of low cost, high conductivity and high stability are achieved. It is suitable for the electrical interconnection of Mini/Micro LED chips and other electronic components.

CN119694665APending Publication Date: 2025-03-25SHANXI HI-TECH VIDEO TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411882267.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The conductive microsphere materials in existing ACFs have problems such as oxidation, high cost, environmental sensitivity and toxicity, resulting in poor long-term stability and reliability of ACFs, especially in electronic connection applications with high stability and reliability.

Method used

A method of preparing conductive particles for titanium oxide core-shell structure is adopted to prepare hydroxy functionalized polystyrene microspheres by one-step method, and titanium oxygen precursors are grown on their surfaces, and finally titanium oxide coated conductive particles are formed by reducing method.

Benefits of technology

It realizes low-cost, strong conductivity, high reliability and high stability conductive particles, suitable for the electrical interconnection of Mini/Micro LED chips, and can be widely used in the electrical interconnection of other electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119694665A_ABST
    Figure CN119694665A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of titanium black core-shell structure conductive particles applied to ACF, and belongs to the technical field of Mini / Micro LED bonding. The preparation method comprises the following steps: firstly, preparing hydroxyl functionalized polystyrene microspheres by a one-step method, and then growing a titanium oxide precursor on the surfaces of the polystyrene microspheres to form Ti4O7 precursor and PS composite microspheres; and finally, preparing the Ti4O7-coated PS conductive particles through a reduction method. The prepared conductive particle is of a core-shell structure, has the advantages of being low in cost, high in conductivity, high in reliability and high in stability, can be used for electrical interconnection of Mini / Micro LED chips and can also be widely applied to electrical interconnection of other electronic components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of Mini / Micro LED bonding technology and relates to a method for preparing titanium dioxide core-shell structure conductive particles used in ACF. Background Art

[0002] Anisotropic Conductive Film (ACF) is an environmentally friendly interconnect material in the modern electronic packaging industry. It is a special film made by dispersing metal-plated microspheres with a diameter of 3~10 μm in a resin insulating hot pressing adhesive. Conductive particles are the core component of ACF and are expected to replace tin-lead solder to achieve the goal of environmentally friendly manufacturing.

[0003] At present, the metal layer materials of the conductive microspheres in ACF mainly use Cu, Ag and Ni, but these materials have some problems that will affect the performance and reliability of ACF. Among them, the surface of Cu is easily oxidized, and the conductivity will decrease in a humid environment; Ag has a high cost and is highly sensitive to sulfides in the environment. Sulfurization reaction may occur, resulting in a decrease in conductivity; Ni has average conductivity and can be toxic under certain environmental conditions. The above problems seriously affect the long-term stability of ACF, especially in electronic connection applications that require high stability and reliability, such as flexible circuits, glass-based Micro LED display circuits and other sensitive electronic devices. Therefore, a new type of conductive material is urgently needed as the conductive layer of ACF to improve the long-term reliability and stability of ACF. Summary of the invention

[0004] The present invention overcomes the shortcomings of the prior art and proposes a method for preparing titanium oxide core-shell structure conductive particles for ACF; solves the problem of poor long-term stability and reliability of ACF; the present invention is achieved through the following technical solutions: A method for preparing titanium oxide core-shell structure conductive particles used in ACF, comprising the following steps: S1. One-step preparation of hydroxyl functionalized polystyrene microspheres: Add sodium dodecyl sulfate and styrene to deionized water, disperse them by ultrasonic at 50-100W for 5-30 minutes, and heat to 40-60°C to obtain solution A; the mass ratio of sodium dodecyl sulfate, styrene and water is 1:150-300:1000-2000; Dissolve potassium persulfate in deionized water to obtain solution B, wherein the concentration of potassium persulfate is 0.01-100 mmol / L; Solution B is added dropwise to solution A to obtain a mixed solution. Under stirring, the mixture is reacted at 50-100°C for 8-12 hours, and then vinyl siloxane is added. The mixture is reacted for 2-4 hours, and then centrifuged, washed, and dried to obtain hydroxyl functionalized polystyrene microspheres. The mass ratio of solution B to solution A is 1:10-500; the mass ratio of vinyl siloxane to the mixed solution is 0.0001%-1%. S2, dispersing hydroxyl functionalized polystyrene microspheres in an organic solvent, adding titanate dropwise into the hydroxyl functionalized polystyrene microsphere solution, the reaction temperature is 50-100°C, the reaction time is 10-14h, so that titanium oxide oligomers grow on the surface of hydroxyl functionalized polystyrene microspheres, centrifuging, washing and drying after the reaction is completed to obtain Ti4O7 precursor @PS composite microspheres with a core-shell structure; the core of the Ti4O7 precursor @PS composite microspheres is polystyrene, and the shell material is Ti4O7; the mass ratio of titanate, hydroxyl functionalized polystyrene microspheres and organic solvent is 1:2-50:50-10000; S3. Put the Ti4O7 precursor@PS composite microspheres into a tubular furnace and introduce a reducing agent at 100-200°C and maintain for 12-36 hours to form sub-titanium oxide core-shell structure conductive particles.

[0005] Preferably, the particle sizes of the hydroxyl-functionalized polystyrene microspheres prepared in step S1 include 500 nm, 1 μm, 2 μm, 3 μm, 4 μm, and 5 μm.

[0006] Preferably, the stirring speed in step S1 is 200-1000 rpm.

[0007] Preferably, the organic solvent in step S2 is an alkane or aromatic hydrocarbon non-polar organic solvent.

[0008] Preferably, the titanate described in step S2 is butyl titanate or isopropyl titanate.

[0009] Preferably, in step S2, the shell material is Ti4O7 with a thickness of 100nm~2000nm.

[0010] Preferably, in step S3, the reducing agent is hydrogen or carbon monoxide or carbon.

[0011] Preferably, the particle size of the titanium oxide core-shell structure conductive particles prepared in step S3 is 500 nm to 7000 nm, wherein the shell thickness is 100 nm to 2000 nm.

[0012] Preferably, when preparing solution B in step S1, potassium persulfate is dissolved in deionized water and mixed at 60-80° C. for 8-12 minutes.

[0013] Preferably, when preparing solution A in step S1, sodium dodecyl sulfate and styrene are added to deionized water, heated to 40-60° C., and maintained for 1-1.5 hours to obtain solution A.

[0014] The beneficial effects of the present invention compared with the prior art are as follows: The present invention first prepares hydroxyl-functionalized polystyrene microspheres, then adopts an in-situ growth method to control the reaction time, reaction temperature and concentration of the precursor, grows a titanium oxide precursor on the surface of the hydroxyl-functionalized polystyrene microspheres, and finally obtains polystyrene conductive particles coated with titanium dioxide by reduction. The conductive particles are core-shell structures, have the characteristics of low cost, strong conductivity, high reliability and high stability, can be used for the electrical interconnection of Mini / Micro LED chips, and can also be widely used in the electrical interconnection of other electronic components. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Schematic diagram of the structure of hydroxyl functionalized polystyrene microspheres (OH-PS) of the present invention; Figure 2 Schematic diagram of the washing process of the present invention; Figure 3 It is a schematic diagram of the drying process of the present invention; Figure 4 is a schematic diagram of the deposition precursor of the present invention; Figure 5 It is a schematic diagram of the PS microspheres after the precursor solution is deposited in the present invention; Figure 6 Schematic diagram of the conductive layer wrapped by PS microspheres of the present invention; Figure 7 This is a schematic diagram of the overall process of black titanium core-shell structure polymer microspheres applied to ACF proposed by the present invention.

[0016] Markings in the figure: 1 is OH-PS, 2 is a sealing cover, 3 is a glass container, 4 is an isopropanol solution, 5 is an oscillating stirrer, 6 is a vacuum drying oven, 7 is a glass stirring rod, 8 is a precursor solution, 9 is a Ti4O7 body solution, 10 is a Ti4O7 conductive layer, and 11 is a Ti4O7@PS conductive particle. DETAILED DESCRIPTION

[0017] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer, the present invention is further described in detail in conjunction with the embodiments and the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The technical solutions of the present invention are described in detail below in conjunction with the embodiments and the accompanying drawings, but the scope of protection is not limited thereto.

[0018] Example 1 This embodiment proposes a titanium dioxide (Ti4O7) core-shell structure conductive particle applied to ACF, which is beneficial to improve the conductivity, reliability and stability of ACF. The process steps are as follows: Figure 7 As shown, the method comprises the following steps: S1. Preparation of hydroxyl functionalized polystyrene (PS) microspheres by one-step method: 0.04 g sodium dodecyl sulfate and 8 g styrene were added to 100 mL deionized water, and ultrasonic dispersion was performed at 100 W for 30 min, and heated to 50 °C and maintained for 1 h to obtain solution A. Dissolve 0.2 g potassium persulfate in 5 mL deionized water and mix at 70 °C for 10 min to obtain solution B; 1 mL of solution B was added dropwise to solution A; 0.1 g of vinyl siloxane was added after reacting at 50°C for 10 h at a stirring speed of 1000 rpm, and the mixture was centrifuged, washed, and dried for 3 h to obtain hydroxyl-functionalized polystyrene microspheres (OH-PS); the hydroxyl-functionalized polystyrene microspheres (OH-PS) obtained were a series of OH-PS microspheres with different particle sizes, with diameters of 500 nm, 1 μm, 2 μm, 3 μm, 4 μm, and 5 μm, respectively, which were achieved by controlling the amount of styrene added, the amount of solvent added, the dispersing power of 100 W, and the stirring speed of 1000 rpm; like Figure 2 As shown, the washing process is to put the centrifuged OH-PS into a glass container 3, add an isopropanol solution 4 into the glass container 3, set a sealing cover 2 on the top of the glass container 3, and then place the entire glass container 3 on an oscillating stirrer 5 for washing; like Figure 3 As shown, the drying process is to discharge the isopropanol solution 4 in the glass container 3 and then place it in a vacuum drying oven for drying.

[0019] The one-step method refers to the preparation and functionalization of insulating microspheres in one pot, which is prepared by controlling the time of adding amphiphilic functional compounds that can copolymerize with styrene.

[0020] S2, OH-PS surface growth titanium oxide precursor: See also Figure 4 , disperse 2 g of hydroxyl functionalized polystyrene microspheres (OH-PS) into 150 mL of n-heptane solution, add 0.1 g of acetic acid, stir for 30 min, add precursor solution 8, which is 1 g of butyl titanate in this embodiment, react at 50 ° C for 12 h, centrifuge, wash, and dry to obtain polystyrene microspheres coated with Ti4O7 precursor, see Figure 5; The core of the Ti4O7 precursor@PS composite microsphere is polystyrene, and the shell material is Ti4O7; the thickness of the shell material Ti4O7 is 800nm.

[0021] S3. Preparation of Ti4O7@PS conductive particles by reduction method: 2 g of Ti4O7 precursor@PS composite microspheres were placed in a magnetic boat, placed in a tube furnace, and a mixture of nitrogen and hydrogen was introduced, wherein the volume ratio of hydrogen was 5%. The temperature of the tube furnace was raised to 120°C and maintained for 12 h to obtain Ti4O7@PS conductive particles. Figure 6 The particle size of the titanium oxide core-shell structure conductive particles is 6000 nm, wherein the shell thickness is 800 nm.

[0022] The Ti4O7@PS conductive particles are used for the preparation of anisotropic conductive adhesive (ACF); the ACF is used for mass welding of MiniLED chips and Micro LED chips to achieve electrical interconnection.

[0023] Example 2 This embodiment proposes a titanium dioxide (Ti4O7) core-shell structure conductive particle applied to ACF, which is beneficial to improve the conductivity, reliability and stability of ACF. The process steps are as follows: Figure 7 As shown, the method comprises the following steps: S1. Preparation of hydroxyl functionalized polystyrene (PS) microspheres by one-step method: 0.04 g sodium dodecyl sulfate and 8 g styrene were added to 100 mL deionized water, and the mixture was ultrasonically dispersed at 50 W for 20 min and heated to 40 °C for 1.5 h to obtain solution A. Dissolve 0.2 g potassium persulfate in 5 mL deionized water and mix at 60 °C for 12 min to obtain solution B; 1 mL of solution B was added dropwise to solution A; stirred, reacted at 100°C for 12 h, 0.1 g of vinyl siloxane was added, and the reaction was continued for 3 h before centrifugation, washing, and drying to obtain hydroxyl-functionalized polystyrene microspheres (OH-PS); the hydroxyl-functionalized polystyrene microspheres (OH-PS) obtained were a series of OH-PS microspheres with different particle sizes, with diameters of 500 nm, 1 μm, 2 μm, 3 μm, 4 μm, and 5 μm, respectively, which were achieved by controlling the amount of styrene added, the amount of solvent added, the dispersing power of 50 W, and the stirring speed of 500 rpm; like Figure 2 As shown, the washing process is to put the centrifuged OH-PS into a glass container 3, add an isopropanol solution 4 into the glass container 3, set a sealing cover 2 on the top of the glass container 3, and then place the entire glass container 3 on an oscillating stirrer 5 for washing; like Figure 3As shown, the drying process is to discharge the isopropanol solution 4 in the glass container 3 and then place it in a vacuum drying oven for drying.

[0024] The one-step method refers to the preparation and functionalization of insulating microspheres in one pot, which is prepared by controlling the time of adding amphiphilic functional compounds that can copolymerize with styrene.

[0025] S2, OH-PS surface growth titanium oxide precursor: See also Figure 4 , 2 g of hydroxyl functionalized polystyrene microspheres (OH-PS) were dispersed in 150 mL of n-heptane solution, 0.1 g of acetic acid was added, and after stirring for 30 min, the precursor solution 8 was added, which was 1 g of butyl titanate in this embodiment, and after reacting at 100 ° C for 14 h, the solution was centrifuged, washed, and dried to obtain polystyrene microspheres coated with Ti4O7 precursor, see Figure 5 ; The core of the Ti4O7 precursor@PS composite microsphere is polystyrene, and the shell material is Ti4O7; the thickness of the shell material Ti4O7 is 800nm.

[0026] S3. Preparation of Ti4O7@PS conductive particles by reduction method: 2g of Ti4O7 precursor@PS composite microspheres were placed in a magnetic boat, placed in a tube furnace, and a mixture of nitrogen and hydrogen was introduced, wherein the volume ratio of hydrogen was 5%. The temperature of the tube furnace was raised to 200℃ and maintained for 36h to obtain Ti4O7@PS conductive particles. Figure 6 The particle size of the titanium oxide core-shell structure conductive particles is 7000 nm, wherein the shell thickness is 1000 nm.

[0027] Example 3 This embodiment proposes a titanium dioxide (Ti4O7) core-shell structure conductive particle applied to ACF, which is beneficial to improve the conductivity, reliability and stability of ACF. The process steps are as follows: Figure 7 As shown, the method comprises the following steps: S1. Preparation of hydroxyl functionalized polystyrene (PS) microspheres by one-step method: 0.04 g sodium dodecyl sulfate and 8 g styrene were added to 100 mL deionized water, ultrasonically dispersed at 80 W for 5 min, heated to 60 ° C, and maintained for 1 h to obtain solution A; Dissolve 0.2 g potassium persulfate in 5 mL deionized water and mix at 40°C for 12 min to obtain solution B. 1 mL of solution B was added dropwise to solution A; after reacting at 70°C for 8 h, 0.1 g of vinyl siloxane was added, and the reaction was continued for 4 h before centrifugation, washing, and drying to obtain hydroxyl-functionalized polystyrene microspheres (OH-PS); the hydroxyl-functionalized polystyrene microspheres (OH-PS) obtained were a series of OH-PS microspheres with different particle sizes, with diameters of 500 nm, 1 μm, 2 μm, 3 μm, 4 μm, and 5 μm, respectively, which were achieved by controlling the amount of styrene added, the amount of solvent added, the dispersing power of 80 W, and the stirring speed of 800 rpm; like Figure 2 As shown, the washing process is to put the centrifuged OH-PS into a glass container 3, add an isopropanol solution 4 into the glass container 3, set a sealing cover 2 on the top of the glass container 3, and then place the entire glass container 3 on an oscillating stirrer 5 for washing; like Figure 3 As shown, the drying process is to discharge the isopropanol solution 4 in the glass container 3 and then place it in a vacuum drying oven for drying.

[0028] The one-step method refers to the preparation and functionalization of insulating microspheres in one pot, which is prepared by controlling the time of adding amphiphilic functional compounds that can copolymerize with styrene.

[0029] S2, OH-PS surface growth titanium oxide precursor: See also Figure 4 , disperse 2 g of hydroxyl functionalized polystyrene microspheres (OH-PS) into 150 mL of n-heptane solution, add 0.1 g of acetic acid, stir for 30 min, add precursor solution 8, which is 1 g of butyl titanate in this embodiment, react at 80 ° C for 10 h, centrifuge, wash, and dry to obtain polystyrene microspheres coated with Ti4O7 precursor, see Figure 5 ; The core of the Ti4O7 precursor@PS composite microsphere is polystyrene, and the shell material is Ti4O7; the thickness of the shell material Ti4O7 is 800nm.

[0030] S3. Preparation of Ti4O7@PS conductive particles by reduction method: 2g of Ti4O7 precursor@PS composite microspheres were placed in a magnetic boat, placed in a tube furnace, and a mixture of nitrogen and hydrogen was introduced, wherein the volume ratio of hydrogen was 5%. The temperature of the tube furnace was raised to 100℃ and maintained for 20h to obtain Ti4O7@PS conductive particles. Figure 6 The particle size of the titanium oxide core-shell structure conductive particles is 500 nm, wherein the shell thickness is 100 nm.

[0031] The above content is a further detailed description of the present invention in combination with a specific preferred embodiment. It cannot be determined that the specific embodiments of the present invention are limited to this. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the present invention, which should be regarded as belonging to the present invention and the scope of patent protection determined by the submitted claims.

Claims

1. A method for preparing titanium oxide core-shell structure conductive particles for ACF, characterized in that: The following steps are involved: S1. One-step preparation of hydroxyl functionalized polystyrene microspheres: Sodium dodecyl sulfate and styrene were added to deionized water, ultrasonically dispersed at 50-100W for 5-30 minutes, and heated to 40-60°C to obtain solution A; The mass ratio of sodium dodecyl sulfonate, styrene and water is 1:150~300:1000-2000; Dissolve potassium persulfate in deionized water to obtain solution B, wherein the concentration of potassium persulfate is 0.01-100 mmol / L; Solution B is added dropwise to solution A to obtain a mixed solution. Under stirring, the mixture is reacted at 50-100°C for 8-12 hours, and then vinyl siloxane is added. The mixture is reacted for 2-4 hours, and then centrifuged, washed, and dried to obtain hydroxyl functionalized polystyrene microspheres. The mass ratio of solution B to solution A is 1:10-500; the mass ratio of vinyl siloxane to the mixed solution is 0.0001%-1%. S2, dispersing hydroxyl functionalized polystyrene microspheres in an organic solvent, adding titanate dropwise into the hydroxyl functionalized polystyrene microsphere solution, the reaction temperature is 50-100°C, the reaction time is 10-14h, so that titanium oxide oligomers grow on the surface of hydroxyl functionalized polystyrene microspheres, centrifuging, washing and drying after the reaction is completed to obtain Ti4O7 precursor @PS composite microspheres with a core-shell structure; the core of the Ti4O7 precursor @PS composite microspheres is polystyrene, and the shell material is Ti4O7; the mass ratio of titanate, hydroxyl functionalized polystyrene microspheres and organic solvent is 1:2-50:50-10000; S3. Put the Ti4O7 precursor@PS composite microspheres into a tubular furnace and introduce a reducing agent at 100-200°C and maintain for 12-36 hours to form sub-titanium oxide core-shell structure conductive particles.

2. The method for preparing titanium oxide core-shell structure conductive particles for ACF according to claim 1, characterized in that: The particle sizes of the hydroxyl-functionalized polystyrene microspheres prepared in step S1 include 500 nm, 1 μm, 2 μm, 3 μm, 4 μm, and 5 μm.

3. The method for preparing titanium oxide core-shell structure conductive particles for ACF according to claim 1, characterized in that: The stirring speed in step S1 is 200-1000 rpm.

4. The method for preparing titanium oxide core-shell structure conductive particles for ACF according to claim 1, characterized in that: The organic solvent in step S2 is an alkane or aromatic hydrocarbon non-polar organic solvent.

5. The method for preparing titanium oxide core-shell structure conductive particles for ACF according to claim 1, characterized in that: The titanate described in step S2 is butyl titanate or isopropyl titanate.

6. The method for preparing titanium oxide core-shell structure conductive particles for ACF according to claim 1, characterized in that: In the step S2, the shell material is Ti4O7 with a thickness of 100nm~2000nm.

7. The method for preparing titanium oxide core-shell structure conductive particles for ACF according to claim 1, characterized in that: In step S3, the reducing agent is hydrogen or carbon monoxide or carbon.

8. The method for preparing titanium oxide core-shell structure conductive particles for ACF according to claim 1, characterized in that: The particle size of the titanium oxide core-shell structure conductive particles prepared in step S3 is 500nm-7000nm, wherein the shell thickness is 100nm-2000nm.

9. The method for preparing titanium oxide core-shell structure conductive particles for ACF according to claim 1, characterized in that: When preparing solution B in step S1, potassium persulfate is dissolved in deionized water and mixed at 60-80° C. for 8-12 minutes.

10. The method for preparing titanium oxide core-shell structure conductive particles for ACF according to claim 1, characterized in that: When preparing solution A in step S1, sodium dodecyl sulfate and styrene are added to deionized water, heated to 40-60° C., and maintained for 1-1.5 hours to obtain solution A.